1990
DOI: 10.1007/bf02072073
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy and multicore myopathy with accumulation of intermediate filaments

Abstract: A girl affected by a restrictive cardiomyopathy with neuromuscular involvement is described. Morphological examination showed a pattern of multicore myopathy and with electron microscopy a sarcoplasmic accumulation of electron dense granular and filamentous material was demonstrated both in skeletal muscle and heart. This peculiar electron dense material corresponded to increased desmin in muscle and cardiac fibres and was demonstrated immunohistochemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Therefore, the partial disruption of intercalated discs in plectin-deficient mice may reflect an increased fragility of desmosomes, assuming that plectin molecules mechanically strengthen these structures similar to hemidesmosomes. Interestingly, in some studies, minicore/multicore diseases were found to be associated with cardiomyopathy (Magliocco et al 1989;Bertini et al 1990), which was at least in one case associated with abnormal accumulation of IFs (Bertini et al 1990). It is therefore tempting to speculate that a common molecular mechanism involving plectin exists for these myopathies.…”
Section: Is Plectin Involved In Diseases Other Than Ebs-md?mentioning
confidence: 99%
“…Therefore, the partial disruption of intercalated discs in plectin-deficient mice may reflect an increased fragility of desmosomes, assuming that plectin molecules mechanically strengthen these structures similar to hemidesmosomes. Interestingly, in some studies, minicore/multicore diseases were found to be associated with cardiomyopathy (Magliocco et al 1989;Bertini et al 1990), which was at least in one case associated with abnormal accumulation of IFs (Bertini et al 1990). It is therefore tempting to speculate that a common molecular mechanism involving plectin exists for these myopathies.…”
Section: Is Plectin Involved In Diseases Other Than Ebs-md?mentioning
confidence: 99%
“…There has been no previous report of multicore myopathy associated with multiple pterygium syndrome, and the occurrence of cardiac disease in conjunction with multicore myopathy has been described in only a few patients [1,9,15], descriptions of the cardiac pathology being rare. We report a rare case of multicore myopathy associated with multiple pterygium syndrome and hypertrophic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 90%
“…4,10,11,37 Immunofluorescent staining, immunohistochemical studies, and electron microscopy may be necessary for detecting diseases such as eosinophilia-myalgia syndrome, desminopathy, cystinosis, and Fabry's disease. 5,20,25,26,38 In RCMP due to amyloidosis, myocardial biopsy shows interstitial amyloid deposits. 24,39 Immunohistochemical staining determines the type of amyloid.…”
Section: Endomyocardial Biopsymentioning
confidence: 99%
“…Cardiac transplantation was performed in 4% of 94 patients with RCMP during a 68-month follow-up period. 4,38 In atrial fibrillation, oral anticoagulation is indicated to prevent stroke or embolism. 34 …”
Section: Therapymentioning
confidence: 99%